2012
DOI: 10.1007/s00894-012-1586-x
|View full text |Cite
|
Sign up to set email alerts
|

QM study and conformational analysis of an isatin Schiff base as a potential cytotoxic agent

Abstract: Isatin is an important compound from the biological aspect of view. It is an endogenous substance and moreover; various pharmacological activities have been reported for isatin and its derivatives. In-vitro cytotoxic effects of the prepared isatin Schiff bases toward HeLa, LS180 and Raji human cancer cell lines has been reported in our previous work. 3-(2-(4-nitrophenyl)hydrazono) indolin-2-one was found to be the most potent one among the studied compounds (IC(30) =12.2 and 21.8 μM in HeLa and LS-180 cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…Schiff bases form an important class of the most widely used organic compounds and have a wide variety of applications in many fields including analytical, biological, and inorganic chemistry. Schiff bases have gained importance in medicinal and pharmaceutical fields due to a broad spectrum of biological activities like anti-inflammatory [4][5][6][7], analgesic [5][6][7][8], antimicrobial [9,10], anticonvulsant [11], antitubercular [12], anticancer [13,14], antioxidant [15], anthelmintic [16], and so forth. The nitrogen atom of azomethine may be involved in the formation of a hydrogen bond with the active centers of cell constituents and interferes in normal cell processes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases form an important class of the most widely used organic compounds and have a wide variety of applications in many fields including analytical, biological, and inorganic chemistry. Schiff bases have gained importance in medicinal and pharmaceutical fields due to a broad spectrum of biological activities like anti-inflammatory [4][5][6][7], analgesic [5][6][7][8], antimicrobial [9,10], anticonvulsant [11], antitubercular [12], anticancer [13,14], antioxidant [15], anthelmintic [16], and so forth. The nitrogen atom of azomethine may be involved in the formation of a hydrogen bond with the active centers of cell constituents and interferes in normal cell processes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…indolinone NH with Glu915 and two oxygen atoms of nitro group with Arg1049 and Asn921 (Figure 12) [35]. revealed that distal hydroxyl group on the ring D is critical for activity.…”
Section: Figure 11mentioning
confidence: 98%
“…The medicinal utilization and applications Schiff bases and their metal complexes are of growing clinical and commercial significance. Schiff bases were selected significance in medical and pharmacological domain due to an expansive range of biological activities such as anti-inflammatory, 1,2 analgesic, 3,4 antimicrobial, 5 antispasmodic, 6 tuberculosis, 7 anticancer, 8 antioxidants, 9,10 anthelmintic. 11,12 The antioxidant performance of N-amino quinoline-2-one metal complexes versus, hydrogen peroxide radicals was not described.…”
Section: Introductionmentioning
confidence: 99%